The Effect Of Information Access And Facilities On Student Services In The Management Study Program At Muhammadiyah University Of Mamuju - Muh. Iksan; Ramli S; Agus Halim (Jurnal Economic Resource, 2025)
This study aims to analyze the effect of access to information and facilities on student services in the Management Study Program at Muhammadiyah University Mamuju. The background of this study is based on the importance of improving the quality of academic services through the provision of transparent access to information and adequate facilities to create student satisfaction. The research method used was quantitative with accidental sampling technique, involving 95 respondents who were students of the Management Study Program. The research instrument was tested through validity and reliability tests, and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results showed that, partially, the information access variable had a significant effect on student services with a t-value of 2.921 > t-table 1.986 and sig. 0.004 < 0.05. Similarly, facilities have a significant effect with a t-value of 4.162 > t-table 1.986 and sig. 0.000 < 0.05. Simultaneously, information access and facilities have a significant effect on student services with an F-value of 19.350 > F-table 3.095 and sig. 0.000 < 0.05. The coefficient of determination (R²) of 0.296 indicates that the two independent variables are able to explain 29.6% of the variation in student services, while the remaining 70.4% is influenced by other factors outside the scope of this study. This study concludes that access to information and facilities are important factors in improving the quality of student services, although their contribution is relatively weak. Therefore, attention needs to be paid to other factors such as the quality of human resources, organizational management, and service culture to strengthen student satisfaction in the higher education environment